Hubungan Pelaksanaan Patient Safety dengan Tingkat Kepuasan Pasien di Ruang Penyakit dalam RSUD Sekarwangi Kabupaten Sukabumi - Raden Zuhra Aliyah Danial; Erna Safariyah; Mustopa Saeful Alamsyah (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Patient safety is a key aspect in modern healthcare that has a significant impact on quality and patient satisfaction. This study aims to determine the relationship between the implementation of patient safety and the level of inpatient satisfaction in the Aisyah Room of Sekarwangi Hospital, Sukabumi Regency. The research design used was quantitative with a cross-sectional approach. A total of 91 inpatients were selected at random and asked to fill out a structured questionnaire. The results showed that 96.7% of patients rated the implementation of patient safety in the good category and 94.5% stated a high level of satisfaction. The results of statistical analysis using the Pearson Chi-Square test showed a significant relationship (p = 0.000) between patient safety implementation and patient satisfaction. This indicates that improving the quality of patient safety implementation can directly increase patient satisfaction during hospitalization. These findings emphasize the importance of consistent safety strategies and patient-centered nursing services. Hospitals are advised to continue to strengthen patient safety culture through regular training, a transparent incident reporting system, and oversight of standard operating procedures. In addition, management involvement in fostering a work climate that supports safety is needed. The use of information technology in safety reporting and monitoring can also speed up risk identification and follow-up. By prioritizing the principles of prudence and effective communication between medical personnel, the quality of service can be improved comprehensively. This study also implies that efforts to improve safety not only have an impact on reducing medical risks, but also on increasing patients' positive perceptions of hospital services. Periodic evaluations, patient education, and active involvement in medical decision-making are important factors in maintaining and improving the quality of safe, effective, and satisfactory health services.